Composition of the social urban water shortage vulnerability index (SUWSVI) applied to São José dos Campos, SP, Brazil - Ferrer, Luciana Maria; Rodriguez , Daniel Andrés; Forti, Maria Cristina; Andrade, Marcio Roberto Magalhães de; Oliveira, Maria Aparecida de (Sustainability in Debate, 2022)
Mining dams within urban areas are a technological risk because, in the event of an accident, they affect water security. For example, a sand mining dam accident caused an interruption in the water supply in the downstream city of São José dos Campos. Thus, the social vulnerability of the population that suffered from a failure in the drinking water supply was evaluated. A water shortage indicator, the Social Urban Water Shortage Vulnerability Index – SUWSVI, was composed. Variables that best reflect the socioeconomic condition were used: Average Income of Head of Household, Female Head of Household, and Children and Elderly Dependent Ratio. The sensitivity analysis considered the city by geographic regions and zoning classes, considering infrastructure supply and lot size. The results showed that although there are full water supply and sewerage infrastructure (99.6%), the access to water was unequal (39% of the population in the medium SUWSVI range).